Comparative Analysis in The Effectiveness of Real vs. Virtual Labs in Enhancing Students’ Conceptual Understanding of Archimedes’ Principle - Edy, Judeanto; Sutopo, Sutopo; Supriana, Edi (Jurnal Pendidikan Sains, 2024)
This research aimed to investigate the effectiveness of virtual laboratories compared to real laboratories in improving students’ conceptual understanding of Archimedes’ principle. A quantitative approach was employed using a pretest-posttest design. The measurement instrument used in this study was a concept mastery test, consisting of 15 multiple-choice questions. Data were analyzed using an independent sample T-test. The research involved students from two XI IPA classes, each consisting of 33 students. The findings indicated that both virtual and real laboratories in the learning process could enhance students’ conceptual understanding. The study concluded that there was no significant difference between the virtual lab and real lab classes in terms of improving students’ conceptual understanding.DOI: 10.17977/jps.v12i32024p085